Use of the international phonetic alphabet as a didactic resource in enhancing english pronunciation - Guayas Mosquera, Kenner Enrique; Guamán García, Genesis Jailin (Machala: Universidad Técnica de Machala, 2024)
This research study aims to improve the pronunciation of affricate consonants in Third Year BGU students, Parallel B, at the Private Educational Unit Juana de Dios through a reinforcement class system that employs the International Phonetic Alphabet IPA. Students face difficulties in adequately articulating these consonants, making the use of IPA phonetic symbols essential for teaching oral production. The research is conducted within a quantitative paradigm with a pre-experimental design, where the researchers used data collection instruments such as observation, pedagogical tests, and teacher interviews. This allowed for the necessary information to be gathered from the study population, consisting of 30 Third Year BGU students The results obtained demonstrated that the reinforcement class system and phonetic instruction significantly improve the pronunciation of affricate consonants. Finally, it is recommended that English teachers incorporate the International Phonetic Alphabet IPA in their classes to improve the articulation of affricate consonants and carry out didactic activities that promote students' interest, motivation, and active participation.
Este estudio de investigación tiene como objetivo mejorar la pronunciación de las consonantes africativas en los estudiantes de Tercer Año de BGU, Paralelo B, en la Unidad Educativa Particular Juana de Dios, a través de un sistema de clases de refuerzo que emplea el Alfabeto Fonético Internacional IPA. Los estudiantes enfrentan dificultades para articular adecuadamente estas consonantes, por lo que la utilización de símbolos fonéticos del IPA es esencial para la enseñanza de la producción oral. La investigación se desarrolla dentro de un paradigma cuantitativo con un diseño preexperimental; en el cual los investigadores utilizaron instrumentos de recolección de datos como la observación, las pruebas pedagógicas y la entrevista al profesor, lo que permitió recopilar la información necesaria de la población de estudio, conformada por 30 estudiantes de tercer año de BGU. Los resultados obtenidos demostraron que el sistema de clases de refuerzo y la instrucción fonética mejoran significativamente la pronunciación de las consonantes africativas. Finalmente, se recomienda que los profesores de inglés incorporen el Alfabeto Fonético Internacional IPA en sus clases para mejorar la articulación de las consonantes africativas y realicen actividades didácticas que promuevan el interés, la motivación y la participación activa de los estudiantes.
Keywords: PRONUNCIATION; CLASS SYSTEM; METHOD; ARTICULATION